Structural domains within the HIV‐1 mRNA and the ribosomal protein S25 influence cap‐independent translation initiation. (10th June 2016) - Carvajal, Felipe; Vallejos, Maricarmen; Walters, Beth; Contreras, Nataly; Hertz, Marla I.; Olivares, Eduardo; Cáceres, Carlos J.; Pino, Karla; Letelier, Alejandro; Thompson, Sunnie R.; López‐Lastra, Marcelo
Abstract : The 5′ leader of the HIV‐1 genomic RNA is a multifunctional region that folds into secondary/tertiary structures that regulate multiple processes during viral replication including translation initiation. In this work, we examine the internal ribosome entry site (IRES) located in the 5′ leader that drives translation initiation of the viral Gag protein under conditions that hinder cap‐dependent translation initiation. We show that activity of the HIV‐1 IRES relies on ribosomal protein S25 (eS25). Additionally, a mechanistic and mutational analysis revealed that the HIV‐1 IRES is modular in nature and that once the 40S ribosomal subunit is recruited to the IRES, translation initiates without the need of ribosome scanning. These findings elucidate a mechanism of initiation by the HIV‐1 IRES whereby a number of highly structured sites present within the HIV‐1 5′ leader leads to the recruitment of the 40S subunit directly at the site of initiation of protein synthesis. Abstract : Using bicistronic constructs we show that the HIV‐1 mRNA harbors a modular internal ribosome entry site (IRES) that relies on ribosomal protein S25 for its activity. Additionally, we present evidence suggesting that once the 40S ribosomal subunit is recruited to the IRES, translation initiates without the need of ribosome scanning.